Analisis Interaksi dan Engagement Tiktok @ERIKARICHARDO dalam Penguatan Nasionalisme di Era Digital - Junias, Febe Dian; Sari, Dewi Kartika; Herwandito, Seto (Universitas Prof. Dr. Moestopo (Beragama), 2025)
This study investigates audience engagement and creator-audience interaction in nationalism-themed content on the TikTok account @ErikaRichardo. It focuses on two research questions: (1) how audience engagement performs across nationalism-related posts, and (2) how narratives, visual aesthethics, and national symbols stimulate interaction. A mixed-methods sequential explanatory approach was employed, combining quantitative and qualitative stages followed by convergence. Quantitative data were gathered by observing engagement metrics-including views, likes, comments, shares, and saves-to identify content with the highest audience response. The qualitative phase consisted of content observation, comment analysis, and documentation review to explore symbolic expression, emotional narratives, aesthetic elements, and forms of audience participation. The findings reveal that Erika Richardo consistently produces nationalism-themed artwork videos around Indonesia’s Independence Day, utilizing strong visual identity, iconic national symbols, and emotional storytelling to trigger meaningful audience involvement. Engagement peaked in 2023, while audiovisual narratives and symbolic representation were key motivating aspects for participation. The convergence of both data sets supports the relevance of Media Dependency Theory across cognitive, affective, and behavioral dimensions. This research contributes by demonstrating how TikTok functions as a participatory digital space to reinforce national identity, offering insights for digital creators, policymakers, and educators in promoting creative civic communication and strengthening patriotic values online.